Assessing the Accuracy of Electricity Demand Forecasts in Developing Countries - Steinbuks, Jevgenijs (World Bank, Washington, DC, 2017)
This study assesses the accuracy of time-series econometric methods in forecasting electricity demand in developing countries. The analysis of historical time series for 106 developing countries over 1960-2012 demonstrates that econometric forecasts are highly accurate for the majority of these countries. These forecasts significantly outperform predictions of simple heuristic models, which assume that electricity demand grows at an exogenous rate or is proportional to real gross domestic product growth. The quality of the forecasts, however, diminishes for the countries and regions, where rapid economic and structural transformation or exposure to conflicts and environmental disasters makes it difficult to establish stable historical demand trends.